Copyright Protection of Computer Software: A Comparative Study of India and Indonesia - Jened, Rahmi; Raharjo, Ignasius Sumarsono; Kumar, Abhishek; Rathi, Aditya; Sari, Betharia Noor Indah; Zulfah, Shofiy (LAW REFORM, 2026)
Since its invention around fifty years ago, computer technology has drastically changed people's lives. As well as providing various conveniences, the existence of computers has also given rise to a number of legal issues. This research project aims to examine comparative law in the context of copyright protection for computer programs in Indonesia and India. Multiple approaches were used: comparative, statutory, conceptual and case. The results obtained are as follows: (1) In Indonesia, a country with a civil law tradition, the benchmark for protecting authors is a reward system. Meanwhile, India, which has a common law legal tradition, uses a benchmark of copyright on the object of work creation as an incentive system;(2) The standard of copyrightability in Indonesia emphasises originality and creativity to a high degree. India, however, places more emphasis on fixation;(3) Both countries provide automatic protection for computer programs for a term of 50 years;(4) In Indonesia, copyright encompasses both economic and moral rights. India, however, places more emphasis on economic rights;(5) There are limitations and exceptions to author's rights in Indonesia. India has a system of fair use or fair dealing;(6) Copyright infringement can be direct or indirect. In Indonesia, law enforcement includes criminal sanctions in the form of imprisonment and fines. In India, it is mostly based on civil lawsuits and damages.